1994
DOI: 10.1111/j.1151-2916.1994.tb05407.x
|View full text |Cite
|
Sign up to set email alerts
|

Bonelike Hydroxyapatite Induction by a Gel‐Derived Titania on a Titanium Substrate

Abstract: Gel-derived titania coating on commercial pure (c.P.) titanium induces hydroxyapatite formation onto its surface from a simulated body fluid (SBF, a metastable calcium phosphate solution). The induced apatite is similar to bone apatite in that it is poorly crystallized, calcium-deficient, and carbonate-containing. Furthermore, the carbonate (Cog-) groups go into the apatite lattice and lie at the positions of PO:-and OH-to replace these ionic groups, resembling the (COi-) groups of bone apatite. Therefore, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
187
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 327 publications
(190 citation statements)
references
References 18 publications
2
187
0
1
Order By: Relevance
“…They concluded that the change in composition at the surface is related to reactions occurring in aqueous media and this reduction in the Ca/P ratio is most probably associated with the biological behaviour of HA. Furthermore, other workers using XRD to study the initial deposition of inorganic compounds onto hydrated titanium oxide surfaces in body fluid environments have clearly shown that apatite is the calcium phosphate compound deposited [13,14]. Hence, in spite of the possible ambiguity arising from the XPS results, it is reasonable to conclude that HA is the calcium phosphate compound being deposited in the MEM (and MEM + H 2 O 2 ) in this work.…”
Section: Xps Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…They concluded that the change in composition at the surface is related to reactions occurring in aqueous media and this reduction in the Ca/P ratio is most probably associated with the biological behaviour of HA. Furthermore, other workers using XRD to study the initial deposition of inorganic compounds onto hydrated titanium oxide surfaces in body fluid environments have clearly shown that apatite is the calcium phosphate compound deposited [13,14]. Hence, in spite of the possible ambiguity arising from the XPS results, it is reasonable to conclude that HA is the calcium phosphate compound being deposited in the MEM (and MEM + H 2 O 2 ) in this work.…”
Section: Xps Resultsmentioning
confidence: 63%
“…Calcium compounds, especially hydroxyapatite (HA), are known to promote osseointegration and surface treatments that favour the growth of these compounds on titanium and titanium alloys and are the subject of much current research on biomaterials [1,2,[12][13][14]. Many workers studying osseointegration of Ti alloys agreed that the formation of a rougher gel-like layer with a high surface area and increased concentration of Ti-OH surface species, on the outer surface of the passive film of Ti, is important in promoting the growth of apatite [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We see from this figure that some new peaks at 1489.38, 1412.92, 871.59 cm -1 occur after the immersion, which correspond to the characteristic peaks of CO 3 . This means that the new matter of carbonate-apatites, such as like-bone apatites, which are formed in the composite coating arising from SSL in the immersion process, which induces the mineralization and growth of bone apatites [21,22] . This demonstrates again that nano-HA/ZrO 2 gradient coating is existed in this case.…”
Section: The Biological Activity Of the Composite Coatingmentioning
confidence: 99%
“…In opposite to Calcium-phosphate surface modification known from literature, like brushite (CaHPO 4 *2H 2 O) [12,18] or hydroxyapatite (HA, Ca 10 (PO 4 ) 6 (OH) 2 ) [1,16,19,21], we deposited Ca(OH) 2 electrochemically on corundum sandblasted rough titanium surfaces. Primarily the addition of citric acid to the Electrolyte enables the deposition of Ca(OH) 2 .…”
Section: Introductionmentioning
confidence: 99%